Emerging Vectors of Narratology: Toward Consolidation or Diversification? (A Response) (ENTHYMEMA, 2013)
This is a response to the questions asked by Franco Passalacqua and Federico Pianzola as a follow-up of the 2013 ENN conference. The discussions that originated at the conference  were rich and thought-provoking and so the editors of this special section of «Enthymema» decided to continue the dialogue about the state of the art and the future of narratology.
Keywords: Narratology; unnatural narrative; fictionality